a-56=4

Simple and best practice solution for a-56=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a-56=4 equation:


Simplifying
a + -56 = 4

Reorder the terms:
-56 + a = 4

Solving
-56 + a = 4

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + a = 4 + 56

Combine like terms: -56 + 56 = 0
0 + a = 4 + 56
a = 4 + 56

Combine like terms: 4 + 56 = 60
a = 60

Simplifying
a = 60

See similar equations:

| 3x=104 | | 3x-105+89=72 | | 4.1x-9.84=8.2 | | -9/2a=18 | | .2x=1.1 | | 4x-5x=81 | | (X-45)(x-45)+x(x-45)+x=540 | | Y=-35+84 | | E=125n+30n | | 5/6x7/5 | | 1/3x1/4x2/3= | | 7n+n=6 | | 4x^2=100-25y^2 | | 8d-2d+3d+8=3d | | -7(7x+3)-6x=-296 | | 0.11d+6=11 | | 7s=56 | | (X+6)*x=280 | | d=p(1+rt) | | n+11n=6 | | 5(2y-1)=25 | | 3*8-6/2 | | U^3-4u^2+u=0 | | -3(x+2)=-5 | | -11r-3(-6r-6)=-(-11r-10) | | Ix+4I=10 | | 35=7(6x-6)+7(2x-5) | | -68-37=x+40 | | d-7.55=14.95 | | 40x+15y=-60 | | -2(3-2x)-3(x-3)=6 | | 0.5c+2.25=4.75 |

Equations solver categories